Age, eustachian tube function and incidence of conductive hearing loss - P, Ramanjaneyulu; SS, Chandrashekar (Journal of All India Institute of Speech and Hearing)
The anatomy and physiology of the pharyngo-tympanic tube (Eustachian tube) was given out by Eustachius. In his literature on the pharyngo-tympanic tube, he emphasized the importance of this tube in the middle ear functioning. Today the importance of this tube in the middle ear ventilation and also in the process of hearing has been accepted.